EXCHANGE RATE FLUCTUATIONS AND NIGERIA'S CAPITAL ACCOUNT - Odusanya, Ibrahim Abidemi; Adesoye, Adesola Bolaji; Gbadamosi, Ayinla Idris (Jurnal Ekonomi & Studi Pembangunan, 2018)
This paper examines the effect of exchange rate fluctuations on the capital account in Nigeria from 1980 to 2015. The data used for the study were retrieved from the Central Bank of Nigeria Bulletin. The study employed Johansen co-integration test, Error Correction Model (ECM) and Fully Modified Ordinary Least Square (FMOLS). Evidence from the study shows that exchange rate has no effect on the capital account. As a result of the study, production in the Nigerian economy must be encouraged through availability of domestic credit while market determined interest rate should be encouraged to stimulate economic growth and investment